INCLUSIVEEDUCATION CULTURE: ESPECIAL EDUCATION AND THE FORMATIVE PROCESSES OF TEACHERS - Guacira de Azambuja; Carmen Rosane Segatto e Souza; Sílvia Maria de Oliveira Pavão (Editora da Universidade de Santa Cruz do Sul, 2012)
The articlepresents a bibliography research. Its objective is to discuss the formativeprocesses particularities of especial educational teacher by an inclusiveeducational culture. It was found thatexist specifities that mark the formation of special educational teacher. Thesespecificities are origin of historical educational context mark by NacionalPolicy on Inclusive Perspective. This perspective suggest the existence ofother factor that influenced and do influence the special education and theteachers in this area. Among the factors associated to this process are: socioculturalvariants, initial formation and the continuous formation. It's concluded that notjust a challenging proposal in the formation of special educational teacher is enoughto effectively attend the student's educational needs, it's necessary to focusin the special educational 's laws and the development of public policies ofgeneral formation.